Metabolomic insights into infertility: distinct biomarkers in PCOS, DOR, and NOR - Demirel M.; Alim M.; Köktaşoğlu F.; Atakul N.; Güner E.; Işık Aydın A. N.; Kafalı S. N.; Atamer Y.; Selek Ş. (My University, 2025)
Infertility affects approximately 15% of reproductive-age couples, with polycystic ovary syndrome (PCOS) and diminished ovarian reserve (DOR) being major contributors. Metabolomic analysis of follicular fluid provides insights into the underlying metabolic disturbances associated with these conditions. This study aimed to identify metabolic biomarkers distinguishing PCOS, DOR, and normal ovarian reserve (NOR) using an untargeted metabolomics approach. Follicular fluid samples from 119 participants (PCOS: n=39, DOR: n=40, NOR: n=40) were analyzed using liquid chromatography–high-resolution mass spectrometry. Metabolites were identified through HMDB, MassBank, and MoNA databases, with pathway analysis conducted via KEGG. Statistical analysis was performed using R and Python, incorporating one-way ANOVA, t-tests, and Mann-Whitney U tests with False Discovery Rate correction. Significant metabolic alterations were observed across groups, with taurocholate, mycalemide, and N,N-dimethylglycine exhibiting strong discriminatory potential. PCOS patients showed decreased levels of taurocholate and trehalose-6-phosphate, whereas NOR patients had elevated N,N-dimethylglycine and argininosuccinate levels. The DOR group exhibited increased levels of 1-methyl-2-pyrrolidone and haplopine. These findings highlight distinct metabolic signatures in PCOS and DOR, suggesting potential biomarkers that could enhance diagnostic and therapeutic strategies. This study underscores the utility of metabolomics in precision medicine approaches for reproductive health.\"DOR\" in the abstract refers to \"POR\", based on Bologna criteria used in the final version of the study.
Keywords: Tıp; Kimya; Analitik Kimya; Kromatografi; Spektroskopik Yöntemler; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Chemistry; Analytical Chemistry; Chromatographic Analysis; Spectroscopical Methods; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; Klinik Tıp (Med); Temel Bilimler (Sci); Yaşam Bilimleri (Life); Klinik Tıp; Biyoloji ve Biyokimya; Doğa Bilimleri Genel; Tıp Genel & Dahili; Çok Disiplinli Bilimler; Kimya Analitik; Clinical Medicine (Med); Natural Sciences (Sci); Life Sciences (Life); Clinical Medicine; Biology & Biochemistry; Natural Sciences General; Medicine General & Internal; Multidisciplinary Sciences; Chemistry Analytical; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Biyokimya (tıbbi); Tıp (çeşitli); Genel Tıp; Kimya (çeşitli); Genel Kimya; Filtrasyon ve Ayırma; Multidisipliner; Fizik Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Biochemistry (medical); Medicine (miscellaneous); General Medicine; Chemistry (miscellaneous); General Chemistry; Filtration and Separation; Multidisciplinary; Physical Sciences